A New Bacterial Steroid Degradation Gene Cluster in Comamonas testosteroni TA441 Which Consists of Aromatic-Compound Degradation Genes for Seco-Steroids and 3-Ketosteroid Dehydrogenase Genes - Horinouchi, Masae (American Society for Microbiology, 2003)
In Comamonas testosteroni TA441, testosterone is degraded via aromatization of the A ring, which is cleaved by the meta-cleavage enzyme TesB, and further degraded by TesD, the hydrolase for the product of TesB. TesEFG, encoded downstream of TesD, are probably hydratase, aldolase, and dehydrogenase for degradation of 2-oxohex-4-enoicacid, one of the products of TesD. Here we present a new and unique steroid degradation gene cluster in TA441, which consists of ORF18, ORF17, tesI, tesH, ORF11, ORF12, and tesDEFG. TesH and TesI are 3-ketosteroid-Δ(1)-dehydrogenase and 3-ketosteroid-Δ(4)(5α)-dehydrogenase, respectively, which work in the early steps of steroid degradation. ORF17 probably encodes the reductase component of 9α-hydroxylase for 1,4-androstadiene-3,17-dione, which is the product of TesH in testosterone degradation. Gene disruption experiments showed that these genes are necessary for steroid degradation and do not have any isozymes in TA441. By Northern blot analysis, these genes were shown to be induced when TA441 was incubated with steroids (testosterone and cholic acid) but not with aromatic compounds [phenol, biphenyl, and 3-(3-hydroxyphenyl)propionic acid], indicating that these genes function exclusively in steroid degradation.